Osteogenic Property Regulation of Stem Cells by a Hydroxyapatite 3D-Hybrid Scaffold With Cancellous Bone Structure - Xia, He; Dong, Lun; Hao, Min; Wei, Yuan; Duan, Jiazhi; Chen, Xin; Yu, Liyang; Li, Haijun; Sang, Yuanhua; Liu, Hong (Frontiers in Chemistry, 2021)
Cancellous bone plays an indispensable role in the skeletal system due to its various functions and high porosity. In this work, chitosan and hydroxyapatite nanowires (CS@HAP NWs) hybrid nanostructured scaffolds with suitable mechanical properties, high porosity and a fine porous structure were prepared to simulate the 3-dimensional structure of cancellous bone. The 3D-hybrid scaffolds promote cell adhesion and the migration of human adipose-derived stem cells (hADSCs) inside the scaffolds. The cavities in the scaffolds provide space for the hADSCs proliferation and differentiation. Moreover, the various contents of HAP and the induced mechanical property changes regulate the differentiation of hADSCs toward osteoblasts. Overall, cellular fate regulation of hADSCs via rationally engineered HAP-based hybrid scaffolds is a facile and effective approach for bone tissue engineering.